EKSPLORASI ETNOMATEMATIKA PADA AKTIVITAS PENGRAJIN ANYAMAN BAMBU MASYARAKAT MENYUKE - Ayuasari, Kristin Tira; Hartoyo, Agung; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe what ethnomathematics exists in theactivities of woven bamboo craftsmen and to describe whatmathematical concepts are contained in the activities of wovenbamboo craftsmen in the Sukake community. The method used inthis research is descriptive method. This research was conducted inthe Menyuke Community (Setolo Hamlet). Data collectiontechniques in this study are observation, interviews anddocumentation. Data analysis techniques in data analysis activitiesresearchers need to carry out three analytical activities that must becarried out, namely: data reduction (Data Reduction), datapresentation (Display Data), and drawing conclusions/verification(Yusuf, 2014: p.407). From the results of observations andinterviews, the results of this study contained ethnomathematics andmathematics concepts in the activities of woven bamboo craftsmen inthe Menyuke community. namely ethnomathematics activities ofmeasuring and designing while in the concept of mathematics thereare the concepts of set, comparison, measurement, geometricconcepts, comparison and folding symmetry. The conclusionsobtained from this study are ethnomathematics in measuring,designing activities As for the mathematical concepts that appear inthe activities of woven bamboo craftsmen, namely: the mathematicalconcept of set, comparison, the mathematical concept ofmeasurement, the mathematical concept of parallel line geometry.and the mathematical concept of folding symmetry.)